Van der Waals interactions in systems involving gas hydrates - Bonnefoy, Olivier; Gruy, Frédéric; Herri, Jean-Michel (Fluid Phase Equilibria, 2005)
International audience The goal of this work is to quantify the Van der Waals interactions in systems involving gas hydrates. Gas hydrates are crystalline compounds that are often encountered in oil and gas industry, where they pose problems (pipeline plugging. etc.) and represent opportunities (energy resources. gas transport, etc.). We focus on methane hydrate, which is the most common one. and calculate its Hamaker constant. Two methods are used and lead to results in good agreement. The Hamaker, microscopic, approach gives a first estimate of the Hamaker constant of 4.59 x 10(-21) J for the hydrate-water-hydrate system. The Lifshitz, macroscopic, method used in combination with the Kramers-Kronig relationship gives a value of 8.25 x 10(-21) J. The Hamaker constant is also computed for three phases systems (gas hydrate clathrate and liquid water with ice, dodecane, quartz, sapphire, Teflon, metals). The interaction potential in different geometrical configurations is then calculated by a hybrid method and various cases of practical interest are studied.